Pengaturan Tentang Pekerja Migran dan Tanggung Jawab Negara - Fadilah Lay Fatimah Ely; Popi Tuhulele; Dyah Ridhul Airin Daties (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The International Labor Organization (ILO) defines a migrant worker as a person who migrates, or has migrated, from one country to another, with the intention of being employed by someone other than himself, including anyone who is regularly accepted, as a migrant, for a job.Purposes of the Research: To find out how international law regulates the protection of migrant workers and how Indonesia is responsible for Indonesian citizens who are migrant workers. Methods of the Research: This research is a normative legal research with analytical descriptive nature. This research was also carried out or only aimed at written regulations or other legal materials.Results of the Research: The results of this study indicate that the regulation on the protection of migrant workers has been regulated in international instruments, including the Maritime Labor Convention 2006. Furthermore, it is regulated in the ILO Convention 188 concerning the Work in Fishing Convention, then namely the International Convention On The Protection Of The Rights Of All Migrant Workers And Members Of Their Families.